2022
DOI: 10.1177/08901171221113834
|View full text |Cite
|
Sign up to set email alerts
|

Applying User-Centered Design in the Development of a Supportive mHealth App for Women in Substance Use Recovery

Abstract: Purpose and Approach Women in recovery describe stigma, negative treatment, and limited support as barriers to achieving their health and parenting goals. Mobile health technologies carefully tailored to support the unique needs of recovery communities can provide less burdensome alternatives to in-person services for women transitioning out of substance use treatment. An iterative design process integrated women’s interests into the structure, content, and interaction flow of a mobile health (mHealth) app. Se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 44 publications
0
5
0
Order By: Relevance
“…They should also be easy and straightforward to understand and use [ 1 , 4 , 13 , 19 , 40 , 42 , 117 , 135 , 141 , 150 , 193 , 194 , 203 , 208 , 217 , 250 , 252 , 265 , 266 , 273 ], as well as have the ability to be personalized according to patient needs and preferences [ 4 , 13 , 62 , 117 , 208 , 216 , 217 , 220 , 246 ]. Finally, a key property and enabler of the reimbursement of digital therapeutics is their interaction with the target population: they should be co-designed and coimplemented with patients and health professionals to maximize the likelihood of their uptake by the relevant stakeholders, with the recognition of the fact that engagement might differ across population groups in different countries [ 4 , 13 , 19 , 40 , 47 , 56 , 57 , 89 , 129 , 166 , 174 , 189 , 190 , 200 , 214 , 215 , 220 , 230 , 250 ].…”
Section: Resultsmentioning
confidence: 99%
“…They should also be easy and straightforward to understand and use [ 1 , 4 , 13 , 19 , 40 , 42 , 117 , 135 , 141 , 150 , 193 , 194 , 203 , 208 , 217 , 250 , 252 , 265 , 266 , 273 ], as well as have the ability to be personalized according to patient needs and preferences [ 4 , 13 , 62 , 117 , 208 , 216 , 217 , 220 , 246 ]. Finally, a key property and enabler of the reimbursement of digital therapeutics is their interaction with the target population: they should be co-designed and coimplemented with patients and health professionals to maximize the likelihood of their uptake by the relevant stakeholders, with the recognition of the fact that engagement might differ across population groups in different countries [ 4 , 13 , 19 , 40 , 47 , 56 , 57 , 89 , 129 , 166 , 174 , 189 , 190 , 200 , 214 , 215 , 220 , 230 , 250 ].…”
Section: Resultsmentioning
confidence: 99%
“…The goal of the coding process was to extract themes that could be incorporated into the intervention design. A similar analytical approach has been used in other studies in which the purpose of the interviews was to inform intervention development and refinement [ 61 ].…”
Section: Methodsmentioning
confidence: 99%
“…We used a user-centered design process that involved iterative cycles of qualitative data collection and intervention design to align the elements of the intervention with themes extracted from the qualitative data. This approach has been used in other studies [ 61 ] and yields a final product that is reflective of users’ experiences and therefore more relevant and acceptable to users. The following are the specific objectives of this paper: (1) to describe the 2-phase user-centered intervention development process that informed the adaptation of the original e-SBI into the e–SBI-HV, (2) to present specific themes extracted from the user-centered design process that directly informed the e–SBI-HV prototype, and (3) to describe the e–SBI-HV prototype.…”
Section: Introductionmentioning
confidence: 99%
“…Previous research has emphasized the importance of user-centered design 1 processes in developing effective mHealth apps for various health domains, such as self-management of chronic conditions ( 21 , 22 ), mental health ( 23 ), persons living with HIV ( 24 , 25 ), women in substance use recovery ( 26 ), and participants with fall risk ( 27 ). Schnall et al ( 24 ) conducted formative research, which included focus groups, participatory design sessions, and usability evaluations, to guide the development of a health management app for individuals living with HIV.…”
Section: Related Workmentioning
confidence: 99%
“…Their findings demonstrated that a user-centered approach offered a deeper understanding of their target users’ specific requirements and facilitated the creation of an mHealth app that better aligned with user needs. Additionally, Eaves et al ( 26 ) applied user-centered design in developing an mHealth app to support women in substance use recovery. Through an iterative design process, the authors showed that users’ feedback helped tailor an mHealth app to maximize usability, access, and safety for this at-risk population.…”
Section: Related Workmentioning
confidence: 99%